Gypsum as a soil ameliorant for black pepper (piper nigrum L. ) in acid soils of Wayanad - Aloka Y G (Department of Soil Science and Agricultural Chemistry , College of Agriculture, 2016)
The experiment entitled “Gypsum as a soil ameliorant for black pepper (Piper nigrum L.) in acid soils of Wayanad” was carried out with the objectives to study the performance of gypsum as a soil ameliorant in growth and development of black pepper and to evaluate its suitability in promoting root growth into deep soil layers of central plateau of Wayanad. The entire investigation was carried out as three experiments, an incubation experiment at College of Agriculture, Padannakkad and two pot culture studies (Column experiment and Double/dual root experiment) done at KVK, Kannur during 2015- 2016. The soil samples for all three experiments were collected from different soil layers (1 st layer: 0-25 cm, 2 nd layer: 25-50 cm, 3 rd layer: 50-75 cm and 4 th layer: 75-100 cm from top soil surface) of pepper garden of RARS, Ambalavayal. The incubation study was laid out in CRD with 8 treatments, 3 replications each and 3 columns were maintained in each replication, the columns were filled layer wise depicting soil profile. The treatments were T 1 - Ca as gypsum at the rate of 50 per cent of CEC, T 2 - Ca as burnt lime at the rate of 50 per cent of CEC, T 3 - Ca as dolomite at the rate of 50 per cent of CEC, T 4 - Ca as gypsum at the rate of 25 per cent of CEC + burnt lime at the rate of 25 per cent of CEC, T 5 - Ca as gypsum at the rate of 25 per cent of CEC + dolomite at the rate of 25 per cent of CEC, T 6 - Ca as CaCO 3 at the rate of 50 per cent of lime requirement, T 7 - Ca as CaCO 3 at the rate of 100 per cent of lime requirement, T 8 - Control. The results of the experiment revealed that the treatments had a significant influence on available soil nutrient status. Application of gypsum showed increase in pH in the lower soil layers as compared to surface layer. Addition of ameliorants particularly gypsum recorded maximum Ca content in all soil layers as compared to sole application of burnt lime and dolomite. This is attributed to high solubility of gypsum, which permits Ca availability in lower soil layers also. The exchangeable Al, the major ion contributing to surface and subsurface acidity in lateritic soils was found minimum with addition of all soil ameliorants amongwhich the maximum reduction was observed with respect to gypsum treatments. The soil available N, P 2 O 5 , K 2 O contents also showed higher values in all surface and subsurface soil layers in gypsum ameliorated soil columns. The column experiment was conducted with 8 treatments and 3 replication under the design CRD at KVK, Kannur. The black pepper var. Panniyur -1 was planted in each column and the treatments imposed were gypsum at different levels in 5 treatments, Ca as gypsum at the rate of 10, 20, 30, 40 and 50 per cent of CEC (T 1 to T 5 ) and Ca as CaCO 3 in two treatments at the rate 50 and 100 per cent of lime requirement (T 6 and T 7 ) along with one control (T 8 ). The results obtained with respect to biometric observations revealed that T 4 (Ca as gypsum at the rate of 40% of CEC) showed maximum plant height, number of leaves, internodal length, fresh and dry root weight at all the stages of plant growth and was on par with T 5 (Ca as gypsum at the rate of 50% of CEC). The root length was maximum in T 4 at 60 and 120 DAP and later at in 180 DAP T 5 recorded highest root length and was on par with T 4 . The soil analysis of column experiment revealed that the treatments T 5 and T 4 significantly increased soil pH, available N, P 2 O 5 , K 2 O, Ca, S and significantly decreased exchangeable Al due to increased solubility and leaching of gypsum in all four soil layers, hence treatments T 4 and T 5 showed superior plant growth and root proliferation at various stages of plant growth. T 4 and T 5 also recorded highest total N, P, K, Ca, S and lowest total Al accumulation in leaf samples in all stages of plant analysis. The second pot culture study with double root experiment was conducted at KVK, Kannur with similar treatments as in incubation experiment with var. Panniyur -1. The ameliorants were added into one root column in which the sprout emerged. The results with respect to biometric observations differed significantly at different growth stages. The treatment T 5 (Ca as gypsum at the rate of 25 per cent of CEC + dolomite at the rate of 25 per cent of CEC) recorded maximum plant height and number of leaves.The observation on root growth recorded at 60, 120 and 180 DAP differed significantly in both ameliorant treated and the dual untreated columns. In treated columns the treatment T 4 (Ca as gypsum at the rate of 25 per cent of CEC + burnt lime at the rate of 25 per cent of CEC) recorded significantly superior dry root weight at 60, 120 and 180 DAP and fresh root weight at 60 DAP. The treatment T 5 recorded maximum fresh root weight at 120 and 180 DAP. In the case of untreated root columns at 60 DAP T 4 had significant maximum dry root weight, where T 5 had maximum significant effect on fresh root weight. The fresh and dry root weight was significantly influenced by T 6 at 120 and 180 DAP. The root length also showed significance difference, in both treated and untreated columns treatment T 4 at 60 DAP and T 5 at 120 and 180 DAP recorded maximum root length. The soil analysis of double root experiment shows that the gypsum treated (T 1 , T 4 and T 5 ) soils were significantly superior to CaCO 3 and control treatments. The sole gypsum and gypsum in combination with burnt lime and dolomite treated soils showed increased soil pH, available nutrient content and decreased exchangeable Al in all the four soil depths and at each interval of soil analysis. The plant analysis carried out at 60, 120 and 180 DAP showed significance difference, among treatments T 5 and T 4 recorded highest total N, P, K, Ca and S content, where T 4 recorded lowest exchangeable Al and was on par with T 5 . The results of investigation indicated that application of gypsum as an amendment alone or in combination with burnt lime and dolomite reduced the surface and subsurface acidity and increased the available nutrient status in the surface as well as sub surface soil layers, which might have resulted in better root proliferation favouring vigorous plant growth and development of black pepper in acid soils.